# MathSciDoc: An Archive for Mathematician ∫

#### TBDmathscidoc:1701.33055

Acta Mathematica, 3, (1), 289-321, 1883.12
@inproceedings{cte1883sur,
title={Sur L'équation $$\begin{array}{l} \frac{{d^2 y}}{{dx^2 }} + \left[ {2\nu \frac{{k^2 sn x cn x}}{{dn x}} + 2\nu _1 \frac{{sn x dn x}}{{cn x}} - 2\nu _2 \frac{{cn x dn x}}{{sn x}}} \right]\frac{{dy}}{{dx}} = \\ = \left[ {\frac{I}{{sn^2 x}}(n_3 - \nu _2 )(n_3 + \nu _2 + 1) + \frac{{dn^2 x}}{{cn^2 x}}(n_2 - \nu _1 )(n_2 + \nu _1 + 1) + } \right. \\ \left. {\frac{{k^2 cn^2 x}}{{dn^2 x}}(n_1 - \nu )(n_1 + \nu + 1) + k^2 sn^2 x(n + \nu + \nu _1 + \nu _2 )(n - \nu - \nu _1 - \nu _2 + 1) + h} \right]y \\ \end{array}$$ },
author={Cte de Sparre},
url={http://archive.ymsc.tsinghua.edu.cn/pacm_paperurl/20170108202931919533764},
booktitle={Acta Mathematica},
volume={3},
number={1},
pages={289-321},
year={1883},
}

Cte de Sparre. Sur L'équation $$\begin{array}{l} \frac{{d^2 y}}{{dx^2 }} + \left[ {2\nu \frac{{k^2 sn x cn x}}{{dn x}} + 2\nu _1 \frac{{sn x dn x}}{{cn x}} - 2\nu _2 \frac{{cn x dn x}}{{sn x}}} \right]\frac{{dy}}{{dx}} = \\ = \left[ {\frac{I}{{sn^2 x}}(n_3 - \nu _2 )(n_3 + \nu _2 + 1) + \frac{{dn^2 x}}{{cn^2 x}}(n_2 - \nu _1 )(n_2 + \nu _1 + 1) + } \right. \\ \left. {\frac{{k^2 cn^2 x}}{{dn^2 x}}(n_1 - \nu )(n_1 + \nu + 1) + k^2 sn^2 x(n + \nu + \nu _1 + \nu _2 )(n - \nu - \nu _1 - \nu _2 + 1) + h} \right]y \\ \end{array}$$ . 1883. Vol. 3. In Acta Mathematica. pp.289-321. http://archive.ymsc.tsinghua.edu.cn/pacm_paperurl/20170108202931919533764.